2011
DOI: 10.1111/j.1743-6109.2011.02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Sexual Functions in Women with Diabetes

Abstract: Introduction Sexual disorders in women with diabetes mellitus (DM) may not necessarily have only the biological etiology. Aims To establish the mediators of sexual functions in the population of women with DM. Methods Five hundred seventeen females, aged 18–55 years old, were included in a questionnaire-based, cross-sectional study. This is the second part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
10
1
1
Order By: Relevance
“…These results are difficult to relate to other research because the publications are characterized by significant methodological divergence. The incidence of sexual dysfunction in women with diabetes is estimated to amount 14-85% [14,25,26]. According to Jackson's research [27], persistent erectile dysfunction was observed in 34% of patients and in 24% they appeared from time to time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are difficult to relate to other research because the publications are characterized by significant methodological divergence. The incidence of sexual dysfunction in women with diabetes is estimated to amount 14-85% [14,25,26]. According to Jackson's research [27], persistent erectile dysfunction was observed in 34% of patients and in 24% they appeared from time to time.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the patients included in the study had been diagnosed with type 2 diabetes. This can have a significant impact on the emergence of a broad spectrum of disorders of sex life [25,26,28]. The combination of mature age of a patient with the diagnosis of diabetes, strongly multiplies the risk of emergence of various types of sexual problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzlin et al .,[3] discussed that poor control of patients, older age, and longer diabetes duration do not have a significant association with SD Different studies conducted by Doruk et al . [27] Wallner et al .,[8] and Nowosielski et al .,[28] indicated that there is no special risk-factors related to SD in diabetic women. They concluded that higher prevalence of SD in diabetic women can be related to probable confounder variables.…”
Section: Discussionmentioning
confidence: 99%